2017
DOI: 10.1159/000485907
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124 Inhibits Growth and Enhances Radiation-Induced Apoptosis in Non-Small Cell Lung Cancer by Inhibiting STAT3

Abstract: Background/Aims: A growing body of evidence indicates that the abnormal expression of microRNAs (miRNAs) play an important role in sensitizing the cellular response to ionizing radiation (IR). The aim of this study was to investigate whether the expression of miR-124 correlated with radiosensitivity in the context of non-small-cell lung carcinoma (NSCLC). Methods: Quantitative reverse transcription polymerase chain reaction (RT-PCR) was used to quantify miR-124 expression in NSCLC tissues and cell lines. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 32 publications
(30 reference statements)
2
34
0
Order By: Relevance
“…cell invasion and migration by targeting Janus kinase 2. In addition, CD164, LIM homeobox 2, STAT3 and snail family transcriptional repressor 2 have been identified as target genes of miR-124 in NSCLC (16,(21)(22)(23). In the present study, a luciferase reporter gene assay data confirmed that LIMD2 was a direct target gene of miR-124, and the expression of LIMD2 was negatively mediated by miR-124 in NSCLC.…”
Section: Discussionsupporting
confidence: 73%
“…cell invasion and migration by targeting Janus kinase 2. In addition, CD164, LIM homeobox 2, STAT3 and snail family transcriptional repressor 2 have been identified as target genes of miR-124 in NSCLC (16,(21)(22)(23). In the present study, a luciferase reporter gene assay data confirmed that LIMD2 was a direct target gene of miR-124, and the expression of LIMD2 was negatively mediated by miR-124 in NSCLC.…”
Section: Discussionsupporting
confidence: 73%
“…We firstly investigated the roles of radiation on migration and invasion of NSCLC cells. It has been reported that radiation greater than 5 Gy can significantly inhibit the proliferation of NSCLC cells . Our data showed that the radiation of 2 Gy, which had no significant effect on cell proliferation , can significantly inhibit the wound healing of A549 (Fig.…”
Section: Resultssupporting
confidence: 48%
“…In colorectal cancer cells, miR‐451a can regulate the cell proliferation in response to radiation . It has been reported that miR‐124 can enhance the radiation‐induced apoptosis of NSCLC cells via inhibition of STAT3 . Similarly, miR‐144‐5p can enhance the radiosensitivity of NSCLC cells by regulating ATF2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR‐1301 inhibits HCC cell progression by inactivating Wnt/β‐catenin signaling (Yang et al, ). miR‐1301 can suppress tumor cell migration and invasion through targeting p53/UBE4B in cancer cells (B. Wang et al, ; M. Wang et al, ). In addition, lower miR‐1301 expression results in poor survival in patients with glioma (Bai, Hu, Wang, Yin, & Shang, ).…”
Section: Discussionmentioning
confidence: 99%